The lawmaking forms: theoretical and practical issues (International relations and international law Journal, 2019)
Article is devoted to studying the forms of lawmaking and their features in Kazakhstan and abroad. As a rule, in world practice lawmaking can be implemented in three forms: the specialized authorized legislature, the people of the republic on a referendum and a certain person with the delegated powers. Adoption of laws by legislature is the usual, daily used lawmaking form. It is the most widespread, the most important and the lawmaking form providing high degree of responsibility of its participants. Realization of lawmaking by specialized authorized public authority (parliament) it is possible to consider as a fundamental basis of lawmaking, the others – as auxiliary institutes. The second form of lawmaking is national lawmakings. It is very seldom used in legislative practice. The most important aspect, feature of this form is the adoption of acts on the basis of direct will of the people, that is by a referendum. In spite of the fact that the adoption of laws by a referendum very seldom meets the countries of the world, national lawmaking is very important and significant. It is reflection of democratic nature of the state. Other form of lawmaking – creation of laws other not legislative subject within the delegated powers. Feature of this form of lawmaking: the related legislative activity is carried out by the subjects which do not have legislative powers, therefore, legislative activity on the basis of the delegated powers does not belong to an appropriate subject in a type of its direct duties.The purpose of scientific research – to define the main forms of lawmaking used in world practice, the analysis of their importance, features and conditions of regulation by their comparison. The scientific importance of work is that article considers along with the established lawmaking form – lawmakings of Parliament, features of lawmaking in the conditions of the delegated powers, conditions of its emergence and practice of realization, value and the importance of national lawmaking, the reason of its rare application.Key words: lawmaking, national lawmaking, adoption of law on the basis of delegation of powers, the bill, the legislation, legal regulation, national powers, a referendum, democracy.